Formation of 4-hydroxynonenal and further aldehydic mediators of inflammation during bromotrichlorornethane treatment of rat liver cells - Olaf Sommerburg; Tilman Grune; Sabine Klee; Fritz R. Ungemach; Werner G. Siems (Mediators of Inflammation)
Bromotrichloromethane (CBrCl3) treatment is a model for studies on molecular mechanisms of haloalkane toxicity with some advantages compared with CCl4 treatment. The formation of 4-hydroxynonenal and similar aldehydic products of lipid peroxidation, which play a role as mediators of inflammatory processes, was clearly demonstrated in rat hepatocytes treated with CBrCl3. It may be assumed that haloalkane toxicity is connected with the biological effects of those inflammation mediatory aldehydic compounds.